A novel CuBi2O4/polyaniline composite as an efficient photocatalyst for ammonia degradation - Ahmad, Nafees; Anae, Jerry; Khan, Mohammad Zain; Sabir, Suhail; Campo Moreno, Pablo; Coulon, Frederic (Elsevier, 2022)
A novel polyaniline (PANI) coupled CuBi2O4 photocatalyst was successfully synthesized via in situ polymerization of aniline with pre-synthesized CuBi2O4 composites. The structure and morphology of the synthesized CuBi2O4/PANI composite photocatalyst were characterized by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) and the photocatalytic performance were evaluated through degradation process of ammonia in water under visible light irradiation. The resultant CuBi2O4/PANI composite showed exceptional stability as its structure and morphology persisted even after being immersed in water for 2 days. The composite photocatalyst exhibited improved charge transport properties due to the electrical conductivity of the PANI protective layer, leading to enhanced photoelectrochemical activity in water and removal of ammonia. PANI with CuBi2O4 (10% wt) heterostructure was applied for photodegradation of ammonia and exhibited a 96% ammonia removal efficiency (30 mg/l with 0.1 g photocatalyst and 180 min), as compared to PANI (78%) and CuBi2O4 (70%). The degradation was attributed to the efficient charge transfer (e− and h+) and formation of reactive oxygen species upon simulated sunlight exposure. The present work suggests that the CuBi2O4/PANI photocatalyst can be synthesized in a simple process and provides an excellent adsorption capacity, high photocatalytic activity, long term stability, and reusability making it a promising alternative for ammonia removal from wastewater.
Keywords: Photocatalyst; In-situ polymerization; Kinetics; Scavengers; Electron-hole pairs